Penguasaan Tanah di Pulau Kanawa Sebagai Penyangga Taman Nasional Komodo di Labuan Bajo Kabupaten Manggarai Barat Provinsi NTT - Aprianus Mario Deno; I Made Suwitra; Diah Gayatri Sudibya (Fakultas Hukum Universitas Warmadewa, 2022)
Kanawa Island is a buffer for Komodo National Park in Labuan Bajo, West Manggarai Regency, NTT Province which is managed by Italian Investors under the company name Kanawa Island & Resort with the area of Kanawa island being 23 hectares (23 ha). The right to Land Tenure of Kanawa by Investors through the provision of HGB above HPL by the West Manggarai Regency Government with a system of granting management permits in the form of Business Use Rights (HGU) is able to provide benefits and support welfare for the local community. The type of research (socio-legal research) or a legal research method that functions to be able to see the law in a real sense and examine how the law works in society and the facts that exist in a society.